Kinetic study of dry reforming of methane using hybrid DBD plasma reactor over La2O3 co-supported Ni/MgAl2O4 catalyst. (21st April 2020) - Khoja, Asif Hussain; Tahir, Muhammad; Amin, Nor Aishah Saidina; Javed, Adeel; Mehran, Muhammad Taqi
Abstract: A kinetic study on dry reforming of methane (DRM) in hybrid dielectric barrier discharge (DBD) plasma reactor over La2 O3 co-supported Ni/MgAl2 O4 catalyst has been investigated. Three different parametric effects namely specific input energy (SIE), discharge volume (VD ) and feed flow rate corresponding to GHSV (h −1 ) are studied using the modified power-law model. The developed kinetic model indicates instantaneous conversions of CH4 and CO2 are functions of SIE, VD and GHSV. Increasing SIE linearly enhances the conversion of CH4 and CO2, while VD displays a non-linear relation with conversion and selectivity. GHSV also shows a linear relation with instantaneous CH4 and CO2 conversion and selectivity of H2 and CO. The rate constants ( k C H 4, k C O 2 ), determined using the proposed kinetic model and various process parameters, are compared with DRM experimental results for validation. The apparent activation energy (Ea ), calculated for CH4 and CO2 using modified Arrhenius equation, are = 32.6 kJ mol −1  (CH4 ) and Ea  = 35.2 kJ mol −1 (CO2 ), respectively. The modified power-law model is a good preliminary description for future understanding of the overall performance of a hybrid catalytic DBD plasma reactor for DRM. Graphical abstract: Image 1 Highlights: Develop a simplified power law kinetic model for hybrid catalytic DBD plasma DRM. Geometric parameters of DBD reactor are considered in a kinetic model. Rate constants for CH4 and CO2 determined using modified power-law. CH4 and CO2 conversions are functions of SIE, GHSV and VD. Calculated results of the kinetic model fitted –well with experimental results. .